Impact of Metabolic Syndrome on Coronary Microvascular Dysfunction: A Single Center Experience - Sucato, Vincenzo; Madaudo, Cristina; Fazio, Luca Di; Manno, Girolamo; Vadalà, Giuseppe; Novo, Salvatore; Evola, Salvatore; Novo, Giuseppina; Galassi, Alfredo Ruggero (Cardiology and Cardiovascular Medicine, 2023)
Coronary microvascular dysfunction (CMD) represents a widespread condition and a prevalent cause of ischemic heart disease. Total TIMI frame count (TTFC) can be a good indicator of CMD in different populations. The aim of our study was to evaluate the incidence of CMD in different populations such as METS patients compared with diabetic and hypertensive patients. The study was carried out on patients with chest pain and/or positive stress test and angiographically undamaged coronary arteries. Our CMD population was divided into three subgroups; patients with arterial hypertension, patients with type II diabetes mellitus and patients with metabolic syndrome. TIMI Frame Count (TFC) and Myocardial Blush Grade (MBG) are indices used to evaluate the degree of microcirculatory dysfunction, in particular the TIMI frame count and the Myocardial Blush degree. Patients with Mets had worse coronary perfusion indices with a higher TFC than the hypertensive population (LAD TFC 33.1 ± 5.6 vs 28.4 ± 5.6 p = 0.018), (TFC RCA 27.2 ± 5.2 vs 23.1 ± 5.2 p = 0.014) (TFC CX 27.9 ± 5.4 vs 26.9 ± 5.4 p = 0.03). However, no differences were found in the three coronary vessels in terms of MBG which, however, was reduced in both groups (7.1 ± 0.49 versus 7.1 ± 0.6 p-value = 0.04). According to the TTFC patients with Mets had worse coronary perfusion than patients with type II diabetes (LAD TFC 33.1 ± 5.6 vs 30.6 ± 6.2 p = 0.04), (TFC RCA 27, 2 ± 5.2 vs 25 ± 5.3 p = 0.02), (TFC CX 27.9 ± 5.4 vs 27.2 ± 5.6 p = 0.05) while MBG was lower in patients with diabetes. In our study, we observed that patients with MetS had slower coronary blood flow using TFC imaging technique analysis than diabetic or hypertensive patients. These indices could help in the diagnosis and management of CMD.